(untitled) (Indian Journal of Arid Horticulture, 2025)
Fusarium wilt is one of the widespread and important fungal diseases of cucurbit crops in the United States and worldwide. It is caused by the fungal pathogen Fusarium oxysporum f. sp. niveum (Fon) that causes significant yield loss in watermelon. There are many commercial cultivars of watermelon that are resistant to Fon races 0 and 1. However, no edible cultivars resistant to races 2 or 3 have been developed. There is a necessity to understand the genetic and molecular basis of Fusarium wilt resistance for crop improvement. Therefore, exploring genetic and molecular factors to determine the resistance to virulent Fon races 2 and 3 in diverse watermelon genotypes will be useful. The recent advances in marker-assisted selection, genomic selection, whole-genome sequencing, gene-editing tools, and genome-wide association studies provide broader insights for improvement of watermelon varieties. In this review paper, we discuss the biology of the Fusarium wilt pathogen (Fon) of watermelon, the history of the Fusarium wilt disease, inheritance studies on Fusarium wilt, quantitative trait loci mapping, bottlenecks in Fusarium wilt resistance breeding, marker-assisted selection and novel plant breeding tools to improve Fusarium wilt resistance in watermelon. This review paper aims to explore the current efforts, challenges, and suggest potential future research for the management of Fusarium wilt using traditional and molecular breeding tools.